The usual rules - Maynard, Joyce, 1953- (St. Martin's, 2004)
Thirteen-year-old Wendy lives with her mother, stepfather, and younger brother in Brooklyn. Her world is transformed one day in September 2001--her mother goes to work that morning and doesn't come back. Through Wendy's eyes, readers follow her slow and terrible realization that her mother has died, and the family's struggle to move forward with their lives. Wendy's journey takes her to California with her real father where she forges friendships with his cactus-growing girlfriend, a teenage mom, and a sad bookstore owner with an autistic son, and begins to understand the deep love and connection she has with her brother. The Usual Rules is an unexpectedly hopeful story of healing and forgiveness that offers readers a picture of how--out of the rubble--a family rebuilds its life.